Genetic variability and yield potential of three semiexotic maize (Zea mays L.) populations (Bioscience Journal, 2015)
The rapid increase of the maize crop in the last decades in Brazil, mainly in the Central West region, has encouraged the second crop (usually maize after soybean) in the same year. For that reason the need for the exploitation of new sources of germplasm seems to be apparent to attend the challenge to create new cultivars (populations or hybrids) adapted to the extremely varying environments. Following this principle, the objective of the present work was directed to the study of genetic variability and yield potential of three semiexotic populations (CRE-01, CRE-02, CRE-03) under the condition of second crop in the Southwest region of the State of Goiás (Brazil). In addition, one cycle of recurrent selection with half-sib families was completed in each population. Half-sib families from each population (200, 180 and 180, respectively) were evaluated in completely randomized block experiments with three replications in Jataí (GO). Parameters estimates were obtained for ear yield (EY), grain yield (GY), plant height (PH), ear height (EH), ear length (EL) and ear diameter (ED). The population means for GY were 5.68 t/ha, 5.83 t/ha and 5.83 t/ha, which were around 70% of the hybrid check. The coefficients of heritability (family mean basis) varied from 0.36 to 0.70; 0.47 to 0.69; and 0.39 to 0.68 for the respective populations. Estimates of the additive genetic variance for grain yield (g/plant) were 316.1, 266.4 and 258.4; and the expected gain from selection were 11.8%, 10.1% and 9.3%, respectively.